„Tylem wytrwał, tyle wycierpiałem…” Werteriada Carla Ernsta Reitzensteina jako przedmiot odniesień w IV części Dziadów Adama Mickiewicza - Paprocka-Podlasiak, Bogna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2015)
The aim of the article is to complement the research on Dziady, Part IV by Adam Mickiewicz with a previously unexplored question of references to two stanzas from C.E. Reitzenstein’s Lotte bei Werthers Grabe, a youthful work of the poet, which the author of the drama wrongly attributed to Goethe. Considering that the author of this Wertheriad, which was very popular at the turn of the 18th century, is not very well known in the Polish culture, it is necessary to include a few aspects related to his biography. The analysis is concerned with the aesthetics, meaning and idealistic relations that connect Reitzenstein’s poem with Dziady, Part IV. The paper also contains a comparison of the reception of the German poet’s elegy in German-speaking countries and functionalising it in Mickiewicz’s drama.